2022
DOI: 10.3390/biology11010079
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Animal Models of Sodium-Valproate-Induced Autism in Postnatal BALB/c Mice: Whole-Brain Histoarchitecture and 5-HT2A Receptor Biomarker Evidence

Abstract: Autism spectrum disorder (ASD) is characterised by problems with social interaction, verbal and nonverbal communication and repetitive behaviour. In mice, the 14th postnatal day is believed to correspond to the third trimester of human embryonic development and is considered a vital period for central nervous system development. It has been shown that ASD affects 2 to 3 times more male than female individuals. In the present study, ASD was induced in 14 postnatal day (PND) BALB/c mice using valproic acid (VPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 44 publications
(79 reference statements)
2
15
0
Order By: Relevance
“…Therefore, studying sex differences in ASD is an interesting issue. In fact, there are more than 80 papers in PubMed on sex influence in different rodent models of ASD (for example, Gouda et al, 2022 ; Ferreira et al, 2022 ; Arnold and Saijo, 2021 ). For this reason, we have performed all our experiments in male, since mixing both sexes surely would arise a high deviation in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, studying sex differences in ASD is an interesting issue. In fact, there are more than 80 papers in PubMed on sex influence in different rodent models of ASD (for example, Gouda et al, 2022 ; Ferreira et al, 2022 ; Arnold and Saijo, 2021 ). For this reason, we have performed all our experiments in male, since mixing both sexes surely would arise a high deviation in the data.…”
Section: Discussionmentioning
confidence: 99%
“…In research conducted by Gouda et al, male and female mice displayed comparable morphological alterations in the prefrontal cortex and Purkinje cells. In male, but not female, rodents treated with VPA, they noticed alterations in the cerebral cortex, including the frontal cortex temporal lobe and the hippocampus (Gouda et al, 2022). Male mice treated with VPA had more cerebral cortical changes than female mice, according to a study by Gouda et al This could account for male animals' social and behavioral deficits, which confirms our results (Gouda et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In male, but not female, rodents treated with VPA, they noticed alterations in the cerebral cortex, including the frontal cortex temporal lobe and the hippocampus (Gouda et al, 2022). Male mice treated with VPA had more cerebral cortical changes than female mice, according to a study by Gouda et al This could account for male animals' social and behavioral deficits, which confirms our results (Gouda et al, 2022). Due to the active roles that the cerebellum and hippocampus play in learning, motor function, anxiety, social functioning, and emotion, all of which are mainly altered in VPA, abnormalities of these brain regions have been recognized as essential in the pathophysiology of autism disorders (Edalatmanesh et al, 2013; Mirza & Sharma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Immune system‐mediated neuroinflammation lead to defects in synaptogenesis, pruning, cell proliferation, migration, and myelination processes of the nervous system (Reid & Danese, 2020). Clinical and preclinical studies revealed that neuroinflammation is involved in the pathogenesis of ASD (Chan et al, 2020; Gouda et al, 2022).…”
Section: Discussionmentioning
confidence: 99%